Systemic lupus erythematosus presenting with thrombocytopenia: report of a child with positive anticardiolipin antibodies - Kanra, Güler; Erdem, Güliz; Özen, Seza; Anlar, F. Yaşar; Beşbaş, Nesrin; Ceyhan, Mehmet (The Turkish Journal of Pediatrics, 1996)
We report a case of systemic lupus erythematosus initially presenting with thrombocytopenia and diagnosed as immune thrombocytopenic purpura. The patient subsequently developed lymphadenopathy, arthritis and cardiac involvement along with anticardiolipin antibodies. We would like to emphasize the fact that these autoantibodies have a role in the pathogenesis of thrombocyte destruction, and that patients with immune thrombocytopenic purpura should be followed for signs of systemic lupus erythematosus.